Conditional lethal mutants of adenovirus type 2-simian virus 40 hybrids. II. Ad2+ND1 host-range mutants that synthesize fragments of the Ad2+ND1 30K protein. - Grodzicker, T (1976)
Adenovirus type 2 (Ad2) grows 1,000 times less well in monkey cells than in human cells. This defect can be overcome, not only upon co-infection of cells with simian virus 40 (SV40), but also when the relevant part of the SV40 genome is integrated into the adenovirus genome to form an adenovirus-SV40 hybrid virus. We have used the nondefective Ad2-SV40 hybrid virus Ad2+ND1, which contains an insertion of 17% of the SV40 genome, to isolate host-range mutants which are defective in growth on monkey cells although they grow normally on human cells. Like Ad2, these mutants are defective in the synthesis of late proteins in monkey cells. A 30,000-molecular-weight protein (30K), unique to Ad2+ND1-infected cells, can be synthesized in vitro, using Ad2+ND1 mRNA that contains SV40 sequences. 30K is not seen in cells infected with those host-range mutants that are most defective in growth on monkey cells, and translation in vitro of SV40-specific mRNA from these cells produces new unique polypeptides, instead of 30K. Genetic and biochemical analyses indicate that these mutants carry point mutations rather than deletions.